La sécurité privée et le problème de la confiance : l’expérience australienne - Prenzler, Tim (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
The private security industry in Australia, as in many jurisdictions, has been beset by allegations of fraud, abuse of powers and incompetence. These problems are illustrated through trade practices, prosecutions, government inquiries, incident reports and other sources. Causation is analysed in terms of Shapiro's (1987) formulation of the problem of "policing trust". The substantial delegation of responsibility entailed in security work makes it highly vulnerable to exploitation and fraud, and this potential is exacerbated by the inadequate regulation of security services. Mitigation of these problems is suggested though an enhanced partnership approach of government and the security industry to regulatory control, an through an assessment of the benefits of in-house security.